Delay in Diagnosis of Cerebral Venous and Sinus Thrombosis: Successful Use of Mechanical Thrombectomy and Thrombolysis - Christopher T. Shah; Jason J. Rizqallah; Oladoyin Oluwole; Aleksandrs Kalnins; John N. Sheagren (Case Reports in Medicine)
Cerebral venous and sinus thrombosis is a relatively rare condition with a variable presentation that can translate into a difficult workup and a delay in diagnosis and treatment. We describe the successful use of mechanical thrombectomy and thrombolysis in the case of an eighteen-year-old woman that presented with progressive thrombosis of the jugular veins and dural sinuses despite adequate anticoagulation. Our case highlights the need for clinicians to include CVST in the initial differential diagnosis of patients in order to prevent delays and poor outcomes.